Engineered fills proceedings of the conference Engineered fills '93, held on 15-17 September 1993 in Newcastle upon Tyne - Clarke, B.G. (Barry Goldsmith) 1950-; Jones, Colin J.F.P. (Colin John Francis Phillip); Moffat, A.I.B (Thomas Telford, 1993)
These conference proceedings present the state of the art in the development of new materials, revised specifications and improved testing methods. The first section comprises invited papers on highways, dams and specifications. The second section deals with theory and testing. The third section deals with specifications and materials and the fourth section covers case histories of dams, highways and foundations.